Controlled cortical impact traumatic brain injury in 3xTg-AD mice causes acute intra-axonal amyloid-β accumulation and independently accelerates the development of tau abnormalities - Tran, Hien T; LaFerla, Frank M; Holtzman, David M; Brody, David L (The Journal of neuroscience, 2011)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized pathologically by progressive neuronal loss, extracellular plaques containing the amyloid-β (Aβ) peptides, and neurofibrillary tangles composed of hyperphosphorylated tau proteins. Aβ is thought to act upstream of tau, affecting its phosphorylation and therefore aggregation state. One of the major risk factors for AD is traumatic brain injury (TBI). Acute intra-axonal Aβ and diffuse extracellular plaques occur in ∼30% of human subjects after severe TBI. Intra-axonal accumulations of tau but not tangle-like pathologies have also been found in these patients. Whether and how these acute accumulations contribute to subsequent AD development is not known, and the interaction between Aβ and tau in the setting of TBI has not been investigated. Here, we report that controlled cortical impact TBI in 3xTg-AD mice resulted in intra-axonal Aβ accumulations and increased phospho-tau immunoreactivity at 24 h and up to 7 d after TBI. Given these findings, we investigated the relationship between Aβ and tau pathologies after trauma in this model by systemic treatment of Compound E to inhibit γ-secretase activity, a proteolytic process required for Aβ production. Compound E treatment successfully blocked posttraumatic Aβ accumulation in these injured mice at both time points. However, tau pathology was not affected. Our data support a causal role for TBI in acceleration of AD-related pathologies and suggest that TBI may independently affect Aβ and tau abnormalities. Future studies will be required to assess the behavioral and long-term neurodegenerative consequences of these pathologies.